Community’s social capital in the management of Mutis Timau Protected Forest in Timor Island, Indonesia: Community’s social capital - Fransiskus Xaverius Dako; RIS HADI PURWANTO; LIES RAHAYU W. FAIDA; SUMARDI (Society for Indonesian Biodiversity, 2019)
Abstract. Dako FX, Purwanto RH, Faida LRW, Sumardi. 2019. Community’s social capital in the management of Mutis Timau Protected Forest in Timor Island, Indonesia. Biodiversitas 20: 2177-2187. The social capital of the community around Mutis Timau Protected Forest in Timor Island is unexplored. In fact, its social capital plays an important role to support sustainable management of the forest viewed from the ability of the community to work together in achieving common goals in groups and organizations. This study aimed to investigate the elements of community’s social capital (i.e. norms, beliefs, and networks) in nine villages located in and around Mutis Timau Protected Forest administratively managed by the Forest Management Unit of South Central Timor District using quantitative survey approach. The result of the study showed that two villages have strong social capital while seven villages have moderate category. Overall, the communities have strong level on the elements of trust in individuals and others, and knowledge and understanding on unwritten rules, but have moderate level on the elements of written rules/regulations, trust in institutions and regulations, organizational network, and participation network. Community participation increases the understanding of written rules, institutional trust and improves the development of social networks (organizational networks and participation) between groups. This results can be used as a reference for the Forest Management Unit of South Central Timor District when developing cooperation with communities that have traditional knowledge and local wisdom through norms, beliefs, and networks in managing and utilizing natural resources in Mutis Timau Protected Forest. Furthermore, the involvement of people with social capital in managing Mutis Timau Protected Forest can maintain forest sustainability and improve community welfare.